Pemberdayaan Ekonomi Lokal di Kelurahan Bencongan Indah, Kabupaten Tangerang: Usaha Pengelolaan Limbah Plastik Menjadi Paving Block - Simatupang, Margareta Theodora; Bantara, Fitaria; Tarigan, Mera Terangta; Nicholine, Nicholine; Behuku, Reyane Dolimariz Putri (SIGn Jurnal Hukum, 2025)
Local economic empowerment represents both a crucial challenge and objective within the implementation of decentralization in Indonesia, demanding innovative regional-level solutions capable of integrating social, economic, and environmental aspects such as waste management. This qualitative case study research aims to analyze the implementation mechanisms and the role of multi-stakeholder collaboration in facilitating economic empowerment through an innovative plastic waste-to-paving block program in Bencongan Indah Urban Village. It also evaluates the program as a practical implementation of decentralization and a potential model for sustainable local development. Primary data were collected through direct observation of business activities and in-depth interviews with the Secretary of the Urban Village, supported by secondary data from documentary studies of regulations and online publications. Data analysis employed a descriptive qualitative approach through content and thematic analysis. Findings indicate that this program transforms plastic waste into an economic product via an observed operational mechanism involving MSMEs/the community, strongly supported by multi-stakeholder collaboration and the facilitation role of the Urban Village Government. The program’s implementation reflects local initiative within the regional autonomy framework and aligns with urban village and regency-level empowerment regulations. Although integrating sustainability pillars and attracting external attention, the program was identified as being in its early stages of development and facing resource and coordination challenges. It is concluded that the Bencongan Indah plastic paving block innovation constitutes a practice of decentralization implementation that facilitates economic empowerment through collaboration, offering a potential, integrative local development model whose sustainability and replicability, however, necessitate strategic management of implementation challenges.